THE INFLUENCE OF FINANCIAL DISTRESS, LEVERAGE, AND FIRM SIZE ON STOCK RETURNS IN THE INFRASTRUCTURE INDUSTRY SECTOR ON THE INDONESIA STOCK EXCHANGE - Widhi Prasetyo Nugroho; Aqamal Haq (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the extent of the influence of financial distress, leverage, and firm size on stock returns of companies in the infrastructure industry sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study employs an explanatory quantitative approach with panel data regression analysis using the Pooled Least Squares (PLS) method. From a total population of 69 companies, 30 companies were selected as the sample using purposive sampling, resulting in 150 observations. Financial distress factors were measured using the Altman Emerging Market Scoring (EMS) approach, leverage was measured by the Debt to Equity Ratio (DER), and firm size was determined by total assets. The results indicate that, partially, only the OPTA variable has a positive and significant effect on stock returns. Meanwhile, WCTA, RETA, BVTL, DER, and firm size do not have a significant effect. Simultaneous testing shows that financial distress, leverage, and firm size collectively have a significant effect on stock returns with a significance level of 0.001. The coefficient of determination (R²) explains only 15% of the variation in stock returns in the infrastructure industry sector, while the remaining 85% is influenced by factors outside the research model.